Simulation performance of effective bandwidth in Wireless Asynchronous Transfer Mode (WATM) network - Wahab, Mat Nazi (2003)
Recently there has been a considerable research interest in the next generation mobile networks. For fixed networks ATM is considered as the enabling technology to handle multi-service traffic. So to ease the transition, as well as aid simple intemetworking, it is natural to use ATM for the mobile network as well. This is a nontrivial task that poses several technical challenges. Most of these challenges arise from the inherent differences between the wired and wireless media and from user mobility in the wireless world. One of the main problems with wireless A TM is overcoming the unreliability of the wireless link in order to maintain quality of service requirements over the wireless portion of the network using error control mechanisms.